Backslopping Time, Rinsing of the Grains During Backslopping, and Incubation Temperature Influence the Water Kefir Fermentation Process - Laureys, David; Leroy, Frédéric; Vandamme, Peter; De Vuyst, Luc (Frontiers in Microbiology, 2022)
Eight series of water kefir fermentation processes differing in backslopping time and rinsing of the grains during each backslopping step, and eight series of fermentation processes differing in incubation temperature and backslopping time were followed for eight backslopping steps. Short backslopping times resulted in high relative abundances of Liquorilactobacillus nagelii and Saccharomyces cerevisiae, intermediate backslopping times in high relative abundances of Leuconostoc pseudomesenteroides, and long backslopping times in high relative abundances of Oenococcus sicerae and Dekkera bruxellensis. When the grains were rinsed during each backslopping step, the relative abundances of Lentilactobacillus hilgardii and Leuc. pseudomesenteroides increased and those of D. bruxellensis and Liql. nagelii decreased. Further, rinsing of the grains during each backslopping step resulted in a slightly higher water kefir grain growth and lower metabolite concentrations. The relative abundances of Liquorilactobacillus mali were highest at 17 °C, those of Leuc. pseudomesenteroides at 21 and 25 °C, and those of Liql. nagelii at 29 °C. With a kinetic modelling approach, the impact of the temperature and rinsing of the grains during the backslopping step on the volumetric production rates of the metabolites was determined.